The big bug hunt. (Economist, 2015)
The article looks at the trend of people engaging in computer hacking to look for Internet security vulnerabilities, or bugs, as an enjoyable past-time and/or to earn money by reporting them to the website owner. Topics include website cookies, Internet browsers, the amount of money Internet firms Google and Facebook have paid to those identifying bugs, and the bug-finding firm Bugcrowd.